1971
DOI: 10.1111/j.1399-3054.1971.tb03484.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Relationship between Various Growth Substances and Bud Production in Funaria hygrometrica. A bioassay for abscisic acid

Abstract: Eleven growth substances were tested for their bud producing capacity in Funaria hygrometrica. IAA and gibberellic acid showed no response, neither did inositol, abscisic acid and adenine. The cytokinins: benzylaminopurine, kinetin and mercaptopurine showed a quantitative relationship while methylaminopurine did not. When different amounts of abscisic acid were added together with 10 μg kinetin (which gave maximal production of buds), there existed a linear relationship between reduction in buds and abscisic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1972
1972
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 8 publications
(2 reference statements)
1
15
0
Order By: Relevance
“…The experiments reported in this paper result in a greatly improved understanding of the inhibition of bud formation in moss by ABA first reported by Valadon and Mummery (1971). The inhibitory effect is not a result of some interference with the initial perception of cytokinin.…”
Section: Aba and The Second Cytokinin-mediated Event In Budmentioning
confidence: 54%
See 1 more Smart Citation
“…The experiments reported in this paper result in a greatly improved understanding of the inhibition of bud formation in moss by ABA first reported by Valadon and Mummery (1971). The inhibitory effect is not a result of some interference with the initial perception of cytokinin.…”
Section: Aba and The Second Cytokinin-mediated Event In Budmentioning
confidence: 54%
“…Exposure to most cytokinins results in log-linear dose-dependent increases in bud number. Stimulation of bud formation can usually be detected at concentrations of ϳ10 Ϫ8 mol/L, and maximal numbers of buds result from exposures to optimal concentrations, usually ϳ10 Ϫ6 mol/L (Brandes and Kende, 1968;Hahn and Bopp, 1968;Valadon and Mummery, 1971).…”
mentioning
confidence: 99%
“…Antagonistic relationship between cytokinin and ABA was demonstrated in an earlier study where application of abscisic acid inhibited the cytokinin-stimulated formation of buds in the moss Funaria hygrometrica (Valadon and Mummery 1971). The induction of shoot buds in the moss Funaria hygrometrica is a classic quantitative bioassay for cytokinins.…”
Section: Introductionmentioning
confidence: 93%
“…Exogenous ABA also inhibits protonemal differentiation to a 'leafy' gametophore. It has been shown that bud formation for the gametophore of Funaria hygrometrica (Valadon and Mummery 1971) and Timmiella anomala (Chopra and Kapur 1989) is inhibited by ABA. This is probably due to the effect of ABA in counteraction with the bud-promoting action of cytokinin (Christianson 2000).…”
Section: Bryophytes and Abamentioning
confidence: 99%